CHARACTERIZATION OF WOMEN’S GENERAL HEALTH AND PHYSICAL ACTIVITY IN FITNESS - Čuprika, Aleksandra; Fernāte, Andra; Čupriks, Leonīds (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Sedentary life causes very big physical and mental health problems, which also decrease one’s life quality. That is why the aim of the research is to evaluate women’s involved in fitness interconnection of subjective evaluation of life quality components and their connection to objective parameters of life quality. GHQ-12 was applied to evaluate general health and IPAQ short version was used to state the amount of physical activities. There are several weak and a very weak correlation between general health, amount of physical activities and the objective factors of life quality. To fully evaluate and improve the parameters of life quality subjective and objective character should be taken into account.